In situ Synthesized Monosodium Urate Crystal Enhances Endometrium Decidualization via Sterile Inflammation During Pregnancy - Zhu, Yu-Yuan; Wu, Yao; Chen, Si-Ting; Kang, Jin-Wen; Pan, Ji-Min; Liu, Xiao-Zheng; Li, Shu-Yun; Yan, Gui-Jun; Liu, Ai-Xia; Huang, Qi-Tao; Yang, Zeng-Ming; Su, Ren-Wei (Frontiers in Cell and Developmental Biology, 2021)
High level of uric acid (UA) is the major origin of gout, and is highly associated with various pregnant complications, such as preeclampsia and gestational diabetes. However, UA's level and role in the very early stage of pregnancy has not been uncovered. This study aims to investigate the relevance of serum UA and decidualization, an essential process for the establishment and maintenance of pregnancy in women and mice during the early stage of pregnancy. In this study, we first proved that expression level of UA synthase xanthine dehydrogenase (XDH) is highly increased along with decidualization of endometrial stromal cells in both in vitro and in vivo models. Furthermore, serum and endometrial levels of UA are higher in mice with decidualized uterin horn and in vitro decidualized stromal cells. The existence of monosodium urate (MSU) crystal was also confirmed by immunostaining. Next, the roles of MSU on decidualization were explored by both in vitro and in vivo models. Our data shows MSU crystal but not UA enhances the decidualization response of endometrial stromal cells, via the upregulation of inflammatory genes such Ptgs2 and Il11. inhibiting of Cox-2 activity abolishes MSU crystal induced higher expression of decidualization marker Prl8a2. At last, in women, we observed enriched expression of XDH in decidua compare to non-decidualized endometrium, the serum level of UA is significantly increased in women in very early stage of pregnancy, and drop down after elective abortion. In summary, we observed an increased serum UA level in the early stage of women's pregnancy, and proved that the increased level of UA results from the expressed XDH in decidualizing endometrium of both human and mouse, leading to the formation of MSU crystal. MSU crystal can enhance the decidualization response via inflammatory pathways. Our study has uncovered the association between UA, MSU, and decidualization during the early stage of pregnancy.